2021
DOI: 10.1093/gji/ggab049
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Bayesian spatial autocorrelation (SPAC) quasi-3-D Vs model of Utah FORGE site with a dense geophone array

Abstract: Summary We expand the application of spatial autocorrelation (SPAC) from typical 1D Vs profiles to quasi-3D imaging via Bayesian Monte-Carlo inversion (BMCI) using a dense nodal array (49 nodes) located at the Utah Frontier Observatory for Research in Geothermal Energy (FORGE) site. Combinations of 4 and 9 geophones in subarrays provide for 36 and 25 1D Vs profiles, respectively. Profiles with error bars are determined by calculating coherency functions that fit observations in a frequency range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Sequentially, the 1D P-wave velocity model from ZVSP was expanded to 3D by correlating with a 3D composite velocity model from [17] and the basement interface (Figure 15). The 3D composite velocity model was contributed from two velocity models, a base model from the quasi-3D VS model of [18] and VP and VS profiles from [7]. A quasi-3D Swave velocity model was constructed [18] by applying spatial autocorrelation (SPAC) over 61 1D VS profiles over an approximately 3.5 km by 3.5 km (11,482.94 ft by 11,482.94 ft) area via Bayesian Monte Carlo inversion (BMCI).…”
Section: Velocity Model Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequentially, the 1D P-wave velocity model from ZVSP was expanded to 3D by correlating with a 3D composite velocity model from [17] and the basement interface (Figure 15). The 3D composite velocity model was contributed from two velocity models, a base model from the quasi-3D VS model of [18] and VP and VS profiles from [7]. A quasi-3D Swave velocity model was constructed [18] by applying spatial autocorrelation (SPAC) over 61 1D VS profiles over an approximately 3.5 km by 3.5 km (11,482.94 ft by 11,482.94 ft) area via Bayesian Monte Carlo inversion (BMCI).…”
Section: Velocity Model Buildingmentioning
confidence: 99%
“…The 3D composite velocity model was contributed from two velocity models, a base model from the quasi-3D VS model of [18] and VP and VS profiles from [7]. A quasi-3D Swave velocity model was constructed [18] by applying spatial autocorrelation (SPAC) over 61 1D VS profiles over an approximately 3.5 km by 3.5 km (11,482.94 ft by 11,482.94 ft) area via Bayesian Monte Carlo inversion (BMCI). Their quasi-3D SPAC VS model provides reliable velocity images with a resolvable depth down to 2.0 km (6561.68 ft).…”
Section: Velocity Model Buildingmentioning
confidence: 99%
“…Assuming our approach is sensitive to this deeper velocity increase would mean that the deeper velocity increase is sharper than the sediment‐to‐granitoid boundary at shallower depths. Using estimated velocities from Zhang and Pankow (2021) and typical densities for sandstone and granite, we estimate the shear impedance contrast of the sediment‐to‐granitoid interface to be IC=26300.17emnormalknormalg/m30.17em30000.17emnormalm/normals20000.17emnormalknormalg/m320000.17emnormalm/normals=1.97 $IC=\frac{2630\,\mathrm{k}\mathrm{g}/{\mathrm{m}}^{\mathrm{3}}\,3000\,\mathrm{m}/\mathrm{s}}{2000\,\mathrm{k}\mathrm{g}/{\mathrm{m}}^{\mathrm{3}}2000\,\mathrm{m}/\mathrm{s}}=1.97$ and would, thus, be too small for our approach. Thus, we conclude that DARE may confirm a deeper increase in velocities.…”
Section: Application To Recorded Ambient Noisementioning
confidence: 99%
“…A single 1-D anisotropic velocity model with three layers was used in the forward model. The Swave velocity was taken from the FORGE velocity estimates by Zhang and Pankaw [61] and Wamriew et al [51], while the P-wave velocities and the densities were estimated using the Castagna [62] and Gardner [63] equations, respectively. Relatively high Thomsen anisotropic parameters [64] of ϵ = 0.51, γ = 0.36, and σ = 0.25, were chosen since previous studies have revealed that a neural network, trained on high anisotropic parameters, would generalize well when presented with waveforms from lower anisotropic models [48].…”
Section: Training Datasetmentioning
confidence: 99%